UPAYA MENINGKATKAN HASIL KETEPATAN TEKNIK SHOOTING BASKET DENGAN METODE KOMBINASI PERMAINAN TARGET PADA SISWA KELAS X 3 SMA NEGERI 7 KEDIRI - Indra Yunika Dwi Cahya; Budiman Agung Pratama; Miftahkodin Miftahkodin (JURNAL ILMIAH NUSANTARA, 2025)
This study began with problems in learning basketball games for class X students of SMAN 7 Kediri. It was found that the level of accuracy of throwing the ball into the basketball hoop was still low, which was caused by the lack of motivation and seriousness of students in participating in learning. The purpose of this study was to improve the accuracy of throwing the ball into the basketball hoop and to increase the motivation and seriousness of students in learning through a combination of target games. This study is a Classroom Action Research (CAR) which was carried out collaboratively and participatory. The subjects of the study consisted of 36 class X-3 students of SMAN 7 Kediri, with 18 male students and 18 female students. The data obtained were analyzed using quantitative and qualitative descriptive techniques. The results of the study showed that the combination of target games can improve the results of the accuracy of throwing the ball into the basketball hoop and increase the motivation and seriousness of students in learning. This can be seen from the increase in student motivation and seriousness as well as the increase in the results of the accuracy of throwing the ball / shooting into the basketball hoop so that the completion reached 94.3% in the second cycle.